Comparison of the McGrath video laryngoscope and macintosh direct laryngoscope in obstetric patients: A randomized controlled trial - Toker, Melike Korkmaz (Pak J Med Sci, 2019)
OBJECTIVE: In obstetric patients’ airway, guidelines have recommended the availability of advanced airway equipment. Our aim was to compare the larynx visualization provided by the Macintosh direct laryngoscope and McGrath video laryngoscope and the intubation time of patients undergoing cesarean section. METHODS: This study was conducted at a private obstetrics and gynecology hospital during one month between June and July 2018. A hundred patients scheduled for elective cesarean section under general anesthesia were randomized into two different group’s as intubated using either McGrath VL or Macintosh DL. The intubation times, Cormack–Lehane grade, percentage of glottic opening, mean arterial blood pressure, and heart rates before and after intubation were compared among the groups. RESULTS: The McGrath VL significantly reduced the intubation time compared to the Macintosh DL. In the McGrath VL group, better glottic view set the time of tracheal intubation as assessed using the Cormack-Lehane classification system and POGO scores were recorded. After intubation, hemodynamic parameters were significantly higher in the Macintosh DL group than in the McGrath VL group. CONCLUSION: The McGrath VL significantly lowered intubation time relative to the Macintosh DL, which may be a critical finding considering the importance of maintaining the mother’s airway for the health of both mother and baby.